Legal Protection for Women as Victims of Domestic Violence Based on Article 1 of Law No. 23 of 2004 - Cindra Ningsih Kohongia (Estudiante Law Journal, 2023)
This study aims to analyze and find out the implementation and implementation of women's protection related to Law Number 23 of 2004 where families are harmonious, happy and love each other. It is everyone's goal to carry out their household life as expected. The results of the study show that family conflict has always been a supporting factor for the occurrence of acts of domestic violence, among which there are still many people who do not understand that if a conflict occurs, women and children are very vulnerable to becoming victims. This happens because the thought that everything that happens within the family sphere is a secret that cannot be known by the public (other people) and it is a disgrace for a husband and wife to tell about their household problems. Even so, violence is often used to describe behavior, both open violence where violence is seen, for example in fights. violence is closed, hidden, not done directly, as in threatening behavior.